2019
DOI: 10.15294/jejak.v12i2.17828
|View full text |Cite
|
Sign up to set email alerts
|

The Influence Of Small Micro Industries On Economic Growth

Abstract: The purpose of this study to determine whether SMEs have a role to economic growth and how big the role of SMEs to economic growth in Indonesia. Types of data used are time series data i.e SMEs data and Economic growth data from year 2003 until 2018 in Indonesia.Tool of analyze data used in this research is multiple linear regression. The result of analysis shows that the influence between of SMEs on economic growth in Indonesia is only 12,5%, it means that Small Micro Entreprises do not have a significant inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
0
10
1
Order By: Relevance
“…Micro, small and medium enterprises (MSMEs) play a vital role in economic development and growth, especially in Indonesia. It is widely recognized that MSMEs are very important because of their main characteristics that distinguish them from large enterprises, especially because MSMEs are labour-intensive enterprises, exist in all locations, especially in rural areas, are more dependent on local raw materials, and are the main providers of goods and services (Rohadin & Yanah, 2019). It is often stated that common things often occur in most MSMEs in Indonesia is that the business management that is more individual in nature and involves family and its relatives.…”
Section: Business Competition In the Era Of Technology: Shifting The ...mentioning
confidence: 99%
“…Micro, small and medium enterprises (MSMEs) play a vital role in economic development and growth, especially in Indonesia. It is widely recognized that MSMEs are very important because of their main characteristics that distinguish them from large enterprises, especially because MSMEs are labour-intensive enterprises, exist in all locations, especially in rural areas, are more dependent on local raw materials, and are the main providers of goods and services (Rohadin & Yanah, 2019). It is often stated that common things often occur in most MSMEs in Indonesia is that the business management that is more individual in nature and involves family and its relatives.…”
Section: Business Competition In the Era Of Technology: Shifting The ...mentioning
confidence: 99%
“…The role of MSMEs are considered as important since half of population of productive residents who work in the informal sector are the peoples who work in MSMEs (Ilegbinosa & Jumbo, 2015). It is expected, the increase of MSMEs productivity could lead to economic growth, through; 1) new job opportunity, 2) the reduction of gap in per capita income, and 3) the increase of the goods and service output, produced by the community (Beisengaliyev et al, 2018;Rohadin & Yanah, 2019). The productive residents could become a group that potentially moves the people's economy.…”
Section: The Problem Faced By Msmes Inmentioning
confidence: 99%
“…Aside of having strategic role towards economic development opportunity, in developing countries, MSMEs tends to be more appropriate to become community's economic mover. According Rohadin & Yanah (2019) on the research about the influence of small and medium industries towards economic development, suggested that MSMEs has more resilience towards economic crisis if compared to big industries. In line with previous research, Rusdarti & Kistanti (2018) in their research, indicated that MSMEs has better preparation towards global market competitions.…”
Section: Introductionmentioning
confidence: 99%
“…In several phenomena that the author observes, competition between financial institutions has mushroomed in several places in all corners of the provinces in Indonesia (Purnawan & Adillah, 2020;Rohadin & Yanah, 2019). This competition is very clearly felt and seen, as one example, in Banten Province, Cilegon City, Cilegon Village, there are 2 government financial institutions that compete with each other.…”
Section: Introductionmentioning
confidence: 97%
“…Micro, Small, and Medium Enterprises (MSMEs) are an interesting study material in the Indonesian economy. MSMEs have been proven to be one of the business sectors as the backbone of the national economy in the community because this sector has flexibility and resilience in dealing with economic crises (Rohadin & Yanah, 2019). MSMEs show an important role in the Indonesian economy because they make a major contribution in supporting national income and Gross Domestic Product (Kristiningrum et al, 2021).…”
Section: Introductionmentioning
confidence: 99%